FREQUENCY OF VITAMIN D DEFICIENCY IN PATIENTS WITH CHRONIC KIDNEY DISEASE (The Research of Medical Science Review, 2025)
INTRODUCTIONPrevious literature shows that vitamin D deficiency is not only significantly prevalent in CKD patients but has prognostic implications and grave outcomes including death as well. Very limited research has been done on the frequency of vitamin D deficiency in CKD patients in our local population.OBJECTIVETo determine the frequency of vitamin D deficiency in patients with chronic kidney disease.STUDY DESIGNCross Sectional StudySTUDY SETTINGSDepartment of Nephrology, Pakistan Institute of Medical Sciences, Islamabad.STUDY DURATIONThis study was conducted from 1st May 2023 to 31st October 2023.MATERIALS AND METHODSPatients with chronic kidney disease were enrolled. Confirmation of CKD was done renal function tests and imaging revealing chronic renal parenchymal changes. Vitamin D level was measured in the blood sample of patient. Level less than 30nmol/L (20ng/mL) was considered confirmatory for the presence of vitamin D deficiency.RESULTSA total of 186 patients were enrolled. Age of the patients ranged from 20 to 60 years. Mean age of the patients was 39.80 ± 5.245 years. Male to female ratio was 2.6:1. Vitamin D deficiency was observed in 130 patients (69.9%).CONCLUSIONVitamin D deficiency is common in patients with chronic kidney disease. Patients with chronic kidney disease should be screened for vitamin D deficiency and treated accordingly.